ANALISIS PERPINDAHAN TIANG PANCANG DERMAGA TIPE MARGINAL WHARF AKIBAT BEBAN SEISMIK DENGAN SIMPLIFIED METHOD DAN TIME HISTORY PADA DERMAGA PETI KEMAS DI KABUPATEN SORONG PROVINSI PAPUA BARAT - Made Novia Kusumayani, Ni
Indonesia is a country with great potential earthquake hit. Therefore, it is important to do seismic analysis for any building structure in Indonesia. One of the structure is wharf which plays an important role in the economy of the country. POLB mentioned that the minimum base for seismic analysis in wharf is to compare the seismic displacement demand and capacity displacement of the structure. This report will explain the analysis of structural displacement demand and displacement capacity of wharf in Sorong, West Papua. The method used to calculate the displacement demand is a non-linear time history analysis (NLTHA) by SAP2000 version 14. That method is the most suitable method for wharf in this resport because the type of this wharf is marginal wharf which is has a different center of mass and rigidity. These conditions will produce a torque on the structure with the dominant influence of rotation. Meanwhile displacement capacity will be calculated by simplified method. This method developed by Rakesh K. Goel to calculate the displacement ductility capacity of wharf structure. The results and analysis showed that the structure of the wharf capable of receiving earthquake loads 2.3 times El-Centro 1940 earthquake. The lateral displacement of pile is 0.311 m in the x direction and 0.237 m in the y direction. The results of the analysis with the simplified method showed the smallest displacement ductility capacity is 0.367 m. Thus, the structure of marginal wharf in Sorong, West Papua is able to accept the burden of seismic.